Optimization process of moringa oleifera seed extract using artificial neural network (ANN) - Idris Oseni, Munirat; Jami, Mohammed Saedi; Monsur, Hammed Ademola (UTM Press, 2019)
The use of chlorine which causes disinfection of by-products is a major concern especially in the developed countries. There is the need to look for a cheap alternative such as the use of plant material as substitute for chemical disinfectant. Moringa oleifera is an extensively documented plant material used for the treatment of drinking water. Its seed extracts contain active agents that having excellent coagulation properties and exerting in-vitro bactericidal activity. However, lack of available literature on the statistical optimization using artificial neural network (ANN) for inactivation kinetics of the seed extract using different disinfection models is the major aspect that need to be explored. This study was conducted to develop operation parameters using ANN for the seed extracts to be used as disinfectant for water treatment. The optimization process based on statistical experimental design using artificial neural network (ANN) in MATLAB 2012A was used to identify and determine the optimum process conditions. The multivariate regression analysis of the disinfection kinetic models was analyzed using SPSS version 20 and the final application of the optimized process conditions with river water was evaluated. The statistical analysis of optimization results using ANN gave a high coefficient of determination (R2) of 0.9992 and 0.9886 for E.coli. The model developed was verified and the optimum process parameters were 124 mg/L dosage, 65 minutes of contact time, 110 rpm mixing rate for E.coli bacterial strain. The order of reaction followed second order and the inactivation kinetics showed that modified Hom model was best fitted the disinfection process with R2 of 0.711. The findings from the application of the seed extract to river water showed that the removal efficiency for the seed extract with over 99.98% reduction of heterotrophic bacteria after the disinfection process. Hence, the findings of this study showed that defatted Moringa oleifera seed extract using the salt extraction method could be used as a disinfectant. This extract was recommended to be used in small communities and in emergency situations